The Effects of the Perception of Being Recognized by Patients With Alzheimer Disease on a Caregiver's Burden and Psychophysical Health. (September 2018) - Lai, Carlo; Cipriani, Marta; Renzi, Alessia; Luciani, Massimiliano; Lombardo, Luigi; Aceto, Paola
Caring for a patient with Alzheimer disease (AD) represents a real challenge that can have considerable long-term psychological and physical consequences. The aim of this study was to evaluate the impact of the perception of being recognized on both the psychophysical health and the level of burden reported in caregivers of patients with AD. The secondary aim was to evaluate the association between the use of a home care assistance service and the burden and psychophysical health in caregivers. The Caregiver Burden Inventory (CBI), the 36-item Short-Form Health Survey (SF-36), and a visual analog scale (VAS) to evaluate the level of perception of being recognized were administered to 31 caregivers of patients with AD. Data were also collected from patients with AD using the Mini-Mental State Examination (MMSE). The level of perception of being recognized was significantly and negatively correlated with total burden ( r = −0.36; P = .045) and objective burden ( r = −0.53; P = .002). It was also significantly and positively correlated with the MMSE score ( r = 41; P = .02). Regression models showed that only the perception of being recognized, and not MMSE, significantly predicted lower caregiver objective burden scores. Furthermore, the use of a home care assistance service significantly predicted higher caregiver physical functioning. The perception of being recognized by an AD relative significantly predicted the caregiver's objective burden associated with a shortage of time. The use of a home care assistance service also resulted in a promotion in the caregiver's social functioning. Further studies are needed to confirm these results.